The Effectiveness of the Government Regulation Concerning Franchises in Resolving Franchise Business Disputes in Indonesia - Setiadi, Ario Setra (Universitas Pelita Harapan, 2024)
Franchising is a business system that is growing with the current in Indonesia and the legal relationship between the franchiser and the franchisee is regulated in a contract that regulates the rights and obligations of the parties who have a relationship to comply with the contents of the agreement, which if violated can have consequences for the future law according to the agreement in the franchise agreement. Since the enactment of Government Regulation No. 42 of 2007, franchise business disputes still occur in Indonesia, such as abuse of franchisor authority, quality of technical and managerial support provided by franchisors to franchisees, and unfairness in profit sharing between franchisees and franchisees. This study aims to examine the effectiveness of Government Regulation No. 42 of 2007 as a legal basis for resolving franchise business dispute cases in Indonesia. The research method used is normative legal research with a literature study approach. The results showed that Government Regulation No. 42 of 2007 is a regulation that regulates the mechanism for resolving business disputes in Indonesia, including in the case of franchise business disputes. This research also identifies several challenges that may be faced in the application of Government Regulation No. 42 of 2007 in resolving franchise business dispute cases, such as the complexity of the dispute resolution process, limited access to dispute resolution institutions, and low awareness and understanding of business people regarding the dispute resolution mechanism regulated in the regulation. Steps are needed such as counseling and persuasive approaches to franchise business actors regarding the importance of resolving business disputes through the mechanisms regulated in the regulation, monitoring, and evaluation of the dispute resolution process carried out by the appointed institution.